DESIGN OF ENCRYPT ROOM SECURE SYSTEM ON SATKOM LANTAMAL V SURABAYA BASED ON FINGERPRINT AND QUICK RESPONSE CODE - Alexander Victor Bukit; I Nengah Putra; Herdhig Prima Yudha; Muhammad Zulkifli (JOURNAL ASRO, 2020)
Technology and information are currently growing rapidly so that computers are no longer used as a computing tool, but have turned into a machine that has the same ability as the human brain, especially searching on a very large fingerprint database. Supervision through a security system that is designed is very helpful for the performance of the Indonesian Navy code personnel who serve in the communication unit, especially the code room. The Code Room is one of the important rooms specifically used as a place for coding activities for the Indonesian Navy. In addition, the code room also functions as a news center for both confidential and open news. This security system using fingerprint (Fingerprint) and Qrcode (Quick Response Code) is designed to be able to control the door with serial communication from android to microcontroller (wemoss) and personal computer (PC) so that it will move the selenoid (door lock) to open the door on condition fingerprint and qrcode are recognized by the system. The level of success of this security system depends on the user's fingerprint identification and the validity of the data stored in the database. The test results of the security system developed in this final project show a success rate of 98%. This tool is expected to be used as a Security System for the Password Room at the Satkom Lantamal V Surabaya. Keywords: Fingerprint and Quick Response Code